2017
DOI: 10.1111/jcmm.13347
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of combination of berberine and metformin in inhibition of DNMT1 gene expression through interplay of SP1 and PDPK1

Abstract: Berberine (BBR), one of active alkaloid found in the rhizome, exhibited anti‐cancer properties. We have showed that BBR inhibited growth of non‐small cell lung cancer (NSCLC) cells through mitogen‐activated protein kinase (MAPK)‐mediated increase in forkhead box O3a (FOXO3a). However, the in‐depth mechanism underlying the anti‐tumor effects still remained to be elucidated. Herein, we further confirmed that BBR not only induced cell cycle arrest, but also reduced migration and invasion of NSCLC cells. Mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Previously, we demonstrated an important role of PDPK1 in cancer growth with the implication that targeting PDPK1 may be a potential treatment of lung cancer . In line with this, overexpression of PDPK1 in A549PDPK1+/+‐Luc cells not only showed more growth regression, it also significantly resisted the SM‐inhibited growth as compared with the wild‐type A549‐Luc cells (Figure A).…”
Section: Resultssupporting
confidence: 74%
“…Previously, we demonstrated an important role of PDPK1 in cancer growth with the implication that targeting PDPK1 may be a potential treatment of lung cancer . In line with this, overexpression of PDPK1 in A549PDPK1+/+‐Luc cells not only showed more growth regression, it also significantly resisted the SM‐inhibited growth as compared with the wild‐type A549‐Luc cells (Figure A).…”
Section: Resultssupporting
confidence: 74%
“…Berberine increased the expression of caspase-3 and impaired mitochondrial membrane potential to induce cell apoptosis in human gastric cancer cells [ 26 ]. Another study has revealed that Berberine induced cell cycle arrest and inhibited migration and invasion of lung cancer cells [ 27 ]. Baicalein (BX3, MOL002714, OB = 33.52%, DL = 0.21), a flavone present in another ingredient from Arum Ternatum Thunb induced mitochondrial-dependent apoptosis, and blocked S-phase cell cycle in human cisplatin-resistant pancreatic carcinoma cell line CAPAN-2 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, BBR has drawn extensive attention due to its antitumorigenic effects in various types of human cancer cells and animal models (33,34). Treatment with BBR has been reported to act on numerous targets and signaling pathways underlying pathophysiological process, including proliferation, apoptosis, angiogenesis, migration and invasion in a variety of cancer cells (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%